Casual Slaughters and Accidental Judgments : Canadian War Crimes Prosecutions, 1944-1948 - Brode, Patrick (Book collections on Project MUSE., 2014)
Patrick Brode has produced a fascinating study of government hesitancy surrounding war crime prosecutions€in€ Casual Slaughters and Accidental Judgments, a history of Canada's prosecution of war crimes committed during the Second World War.€